Observations on the changing behaviour of AKR mouse lymphomas serially transplanted in the strain of origin - Denton, Pamela M. (1968)
Five spontaneously occurring AKR lymphomas have been separately passaged through a number of generations in isogenic hosts. In each case evidence of increasing malignancy was observed, as judged either by the time of appearance of a leukaemic blood picture or the time taken to kill the host, or both. One tumour, associated with the largest splenic and lymph node weights in the autochthonous host, took four times as long as the other tumours to kill hosts bearing the first transplant generation. Furthermore, in one of the animals bearing the third generation of this lymphoma, a spontaneous regression of the tumour has occurred. It is suggested that these findings are consistent with the initial possession by, and subsequent deletion from the lymphomas, of tumour specific antigens.